World Bank adopts guidelines to include nutrition in irrigation investments - CGIAR Research Program on Water, Land and Ecosystems (2021)
The guidance highlights the pathways through which irrigation improves nutrition, intervention options, and indicators to measure food security and nutrition outcome.